2011
DOI: 10.1016/j.vaccine.2011.02.087
|View full text |Cite
|
Sign up to set email alerts
|

Measles susceptibility in children in Karachi, Pakistan

Abstract: Measles, despite being vaccine preventable is still a major public health problem in many developing countries. We estimated the proportion of measles susceptible children in Karachi, the largest metropolitan city of Pakistan, one year after the nationwide measles supplementary immunization activity (SIA) of 2007–08. Oral fluid specimens of 504 randomly selected children from Karachi, aged 12–59 months were collected to detect measles IgG antibodies. Measles antibodies were detected in only 55% children. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 11 publications
4
30
0
Order By: Relevance
“…At present, the routine immunization schedule in both India and Pakistan includes two doses of measles vaccine. In the Democratic Republic of Congo, Ethiopia and Nigeria, the first dose is given through the routine immunization schedule and the second dose is given through SIA [54,55]. …”
Section: Discussionmentioning
confidence: 99%
“…At present, the routine immunization schedule in both India and Pakistan includes two doses of measles vaccine. In the Democratic Republic of Congo, Ethiopia and Nigeria, the first dose is given through the routine immunization schedule and the second dose is given through SIA [54,55]. …”
Section: Discussionmentioning
confidence: 99%
“…8 This monitoring system is resource-intensive, utilizes convenience sampling and is prone to misreporting bias since the same individuals often supervise both the vaccinations and the evaluation of vaccine coverage. 9 It also exposes the members of the evaluation teams to the risk of violence, especially in certain locations with poor security. More than 16 vaccinators associated with polio vaccination campaigns have been assassinated in various parts of Pakistan since December 2012.…”
Section: Problemmentioning
confidence: 99%
“…5,6 Another study correlating reported vaccination history with serology in Pakistan, revealed that only 54% of the children whose parents reported measles vaccination by recall, actually had serological immunity against measles. 8 Low card retention and parental recall lead to questionable estimation of coverage, 7 hence, vaccination coverage surveys should use them in conjunction.…”
Section: Introductionmentioning
confidence: 99%